서해 근소만-선유도 갯벌 퇴적층의 지온변화에 관한 연구 - 송규민; Song, Kyu-Min (Ocean and polar research, 2013)
The vertical structure of sediment temperatures in the tidal flats of Geunso Bay and Seonyu Island in western Korea were measured for more than a year and analyzed. Mean temperature decreased with depth in spring and summer. On the contrary, it increased with depth in fall and winter, faithfully reflecting the seasonal variation resulting from the heating and cooling of the surface sediment. The surface sediment temperatures are shown to be strongly dependent on solar radiation, M2, and M4 tidal components. They are also weakly affected by precipitation. Thermal diffusivity of sediment is estimated at each depth and in each of the four seasons by applying the amplitude equation method. In Geunso Bay, the estimated seasonal-mean values decreased with depth, while they showed little change in Seonyu Island. Depth-averaged thermal diffusivity in Geunso Bay ($1.94 {×}10^{-7}m^2/s$) was smaller than Seonyu Island ($2.20 {×}10^{-7}m^2/s$). The variability of thermal diffusivity is shown to corelate with sediment composition and sorting from the grain-size analysis of intertidal sediments in Geunso Bay and Seonyu-do.